A theoretical approach to the use of information and communication technologies in Physical Education - Yildiz, K.; Güzel, Pınar; Zerengök, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Today’s fast-changing World imposes new challenges in all aspects of our lives. Most prominent changes have been observed in information and communications technology (ICT). These changes imposed new challenges for the education system, schools, and especially for teachers. Keeping up with the pace of these developments has gained an increased popularity in today’s digital culture, and in consequence academic interest increased significantly on using smart and modern technologies in the field of Physical Education. So far a reasonable amount of research has been done to study technology integration in teaching and learning environments. Yet, more effort needs to be spent for the claims and research within the realm of Physical Education. This paper therefore tries to present a short overview on the topic, the approaches, tools and studies about the use of technology in the field of PE.